Office Interiors and the Fantasy of Information Work - Renyi Hong (tripleC: Communication, Capitalism & Critique)
This essay provides a historical context to the office interiors, describing its capacity to enchant the sphere of work and to transform the subjectivities of workers. Focusing on Florence Knoll and Robert Propst, American designers who contributed to the modern aesthetic in the postwar, I highlight how the sale of offices conveyed a fantasy of information work. Knoll and Propst had marketed their ideas using showrooms, textiles, seminars, and informational materials. These communicative practices emphasized the sensate quality of information work, which coached workers to recognize and interpret the visual, aural, and tactile quality of work environments. By doing so, it tied sensations of pleasure to the prospect of self-transformation, which provides basis for the modern attachment to beautified workspaces.